Encouraging learning difficulties in social studies by multidisciplinary learning models - Ubaidah, Akmal; Kartika, Dinda Rahma; Laili, Nur; Adi, Khofifatu Rohmah (Jurnal Teori dan Praksis Pembelajaran IPS, 2023)
Learning activity distributes knowledge from educators to students to develop abilities and shape character, essential in improving student learning outcomes.  However, there are still many learning activities that are less exciting or tend to be monotonous, which makes students quickly bored. This study aims to explore the learning difficulties in social studies learning by implementing a multidiscipline learning model. A conventional literature review and Jacobs' theory of a multidisciplinary integrated learning model were used to analyze the data.  This study found that applying multidisciplinary learning models in social studies learning could bring some advantages, such as encouraging students to be more open-minded, active, easy-going, friendly, motivated, disciplined, and work in teamwork.